PENERAPAN MODEL LOGICAL FRAME WORKS PROGRAM PEMBERDAYAAN LANSIA DI KECAMATAN KARANGANYAR KABUPATEN PEKALONGAN - Yuniarti Yuniarti (LPPM Universitas Pekalongan, 2015)
The Population of the old ages in year 2020 is projected at 11,34% with a life expectancy reaches 71,1 years olds. It will be a great problem in national development if not taken seriously. This situation encourages empowerment programs achieving welfare for old age physically, mentally, socially and spiritually based promotive and preventive efforts. It’s an exploratory research with a qualitative approach. This study integrate health project /program by implementing logical frame works. The study conducted in the village Kutosari Karanganyar District of Pekalongan. Target of this study are 161 old ages over 60 years olds. The empowerment program for old ages was compiled using Logical Frame Works model. It’s an analytical tool that provides technical instructions a health project/program. Logical Frame Works contains stakeholder analysis, problem analysis and objective analysis. Logical Frame Works analysis result in the form of logframe matrix includes a combination of vertical logic and horizontal logic. Empowerment program for old ages contains activities that are oriented towards healthy behaviour, early detection of disease, treatment of minor ailment and rehabilitative efforts. These activities included medical, psychosocial and educational services. Logical Frame Works effectively compose of planning and evaluating the empowerment programs for old ages. This empowerment based a promotive-preventive health behavior and early detection of health problems. That program aims achieving welfare for old ages according Law Number 13th of 1998. Composing Logical Frame Works oriented to social and cultural aspects as well as the caracteristics of the local community for achieving optimal results. The empowerment programs for old ages implemented in harmony with elderly- friendly paradigm with elderly as a subject of the programs.